The Effect of Innovation, Accessibility and Trust on User Satisfaction of Economy Class Railway Services DAOP IX Probolinggo Station - Pradina, Adelia Fitri; Elmas, Muhammad Syarif Hidayatullah; Nafis, Raihan Wishal (JPIM (Jurnal Penelitian Ilmu Manajemen), 2024)
This study aims to determine the effect of innovation, accessibility and trust on the satisfaction of users of DAOP IX Probolinggo Station economic train services partially. The research method used is quantitative with the independent variables of innovation, accessibility, trust and the dependent variable, namely satisfaction. The population of this study were users of DAOP IX Probolinggo Station economy class train transportation services in January and February 2024. The sampling technique was carried out by purposive sampling method as many as 108 people. The data analysis stage begins with the Validity, Reliability, Classical Assumption Test, Multiple Linear Regression Analysis, Determination Coefficient Test and Hypothesis Test using SPSS Version 26. The results showed that the innovation variable had a positive but insignificant effect on satisfaction, while the accessibility and trust variables had a positive and significant effect on satisfaction.